Modifiable risk factors of vasospastic angina: a systematic literature review - Albalawi, Abdulmajeed F.; Alotaibi, Hamoud T.; Alharbi, Razan K.; Alghamdi, Abdulrahman A.; Alzahrani, Ali A.; Alhamoud, Jwael A.; Alzahrani, Saleem A.; Safhy, Noof Y.; Aqeeli, Reem K.; Hamdhi, Sami M.; Albarrak, Eman N.; Alshammari, Jawza S.; et al. (International Journal Of Community Medicine And Public Health, 2021)
Vasospastic angina is caused by transient coronary spasms unrelated to exertion, which may even occur at rest (classically at night) and promptly responds to short acting nitrates. It is thought to be caused by inherent generalised hyper reactivity of the smooth muscle cells of epicardial vessels to various stimuli. Being comparatively less studied, the risk factors for VSA vary considerably from obstructive or atherosclerotic cardiac disease. However, coronary vasospasm can occur in non stenosed arteries, atherosclerotic arteries as well as sub critically stenosed arteries which can result in significant overlap between the risk factors and underlying pathophysiology. 1-14% of AMI can be caused by non-obstructive, or ‘functional’ coronary artery disorders like vasospastic angina but VSA continues to be underdiagnosed and less well understood than obstructive coronary artery disorders. This prompted us to study the existing literature for modifiable risk factors of coronary artery vasospasm so that an emphasis can be made on proper lifestyle modifications and avoidance of vasospastic agents in susceptible individuals. Smoking proved to be the most important risk factor whereas recreational drugs and drugs used for treatment of certain medical disorders have also been shown to associate with coronary vasospasm. Medical personnel, therefore, need to be more vigilant in history taking as well as investigating cardiac chest pain in which traditional investigations end up being normal so that an early diagnosis of vasospastic angina can be made and appropriate steps taken to improve the quality of life of patients.